The Role of Digital Technologies to Promote Collaborative Creativity in Language Education - Selfa-Sastre, Moisés; Pifarré, Manoli; Cujba, Andreea; Cutillas, Laia; Falguera, Enric (Frontiers in Psychology, 2022)
The importance of cultivating creativity in language education has been widely acknowledged in the academic literature. In this respect, digital technologies can play a key role in achieving this endeavour. The socio-cultural conceptualization of creativity stresses the role of communication, collaboration and dialogical interaction of creative expression in language education. The objective of this paper is to study the literature focusing on cases of collaborative creativity and technology embedded in language education. To this end, we carry out a systematic revision of state-of-the-art literature consisting of 26 blind peer-reviewed empirical studies selected from several databases that address our main research question, namely, which specific roles and forms of digital technology can be identified in the existing literature that support collaborative creativity in language education. Results show that the features of digital technology unfold a range of learning opportunities in language education and can play three different roles in promoting collaborative creativity: (1) as a tutoring device that guides the implementation of key co-creation skills; (2) as a tool that enables and shapes the development of co-creative thinking skills; and (3) as a medium that creates rich and resourceful environments to stimulate the emergence of collective creative processes. The paper also reveals that these three roles can be performed using a wide range of interactive technologies that encourage students to participate in a rich, co-creative language learning experience and equip learners with key competences to approach complex problems in a globalised and hyper-connected world. Finally, this paper may contribute to developing future language technology-enhanced learning projects capable of promoting key collaborative and creative processes.